1998
DOI: 10.1016/s0042-6989(97)00236-8
|View full text |Cite
|
Sign up to set email alerts
|

Judging distance from ocular convergence

Abstract: Subjects misjudge distances considerably when forced to rely on extra-retinal information. Nevertheless, they can reproducibly set a target to the same distance as a reference, or to double or half that distance, even when they have to look back and forth between them because they are prevented from seeing one when looking at the other. Our explanation for this apparent discrepancy is that people have access to reasonably accurate extra-retinal information on changes in ocular convergence, but can only use thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 21 publications
8
59
0
Order By: Relevance
“…Previous studies of binocular vergence have shown that vergence is evaluated in terms of an adaptable reference vergence distance (Brenner & Van Damme, 1998;Mon-Williams & Tresilian, 1999a, 1999bMon-Williams et al, in press;Owens & Liebowitz, 1976;von Hofsten, 1976von Hofsten, , 1979. Repeated observation of an object at a single distance with no other object visible would attract the reference vergence to that distance, rendering vergence as rather poorly specified information about distance.…”
Section: Testing Vision Without Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of binocular vergence have shown that vergence is evaluated in terms of an adaptable reference vergence distance (Brenner & Van Damme, 1998;Mon-Williams & Tresilian, 1999a, 1999bMon-Williams et al, in press;Owens & Liebowitz, 1976;von Hofsten, 1976von Hofsten, , 1979. Repeated observation of an object at a single distance with no other object visible would attract the reference vergence to that distance, rendering vergence as rather poorly specified information about distance.…”
Section: Testing Vision Without Feedbackmentioning
confidence: 99%
“…The relation between vergence and perceived distance is mediated by an adjusted reference level for vergence (Brenner & Van Damme, 1998;Mon-Williams, Tresilian, & Hasking, in press;Owens & Liebowitz, 1976;von Hofsten, 1976von Hofsten, , 1979. The reference vergence level is a function of both luminance level and recently experienced vergence distances (Brenner & Van Damme, 1998;Mon-Williams, Tresilian, & Hasking, in press;Owens & Liebowitz, 1976). With repeated experience of only a single distance, vergence level would become poorly defined as information about distance.…”
mentioning
confidence: 99%
“…In addition, perceived space is typically distorted, with near targets appearing further away than they actually are and far targets appearing closer, a phenomenon referred to as the speci¢c distance tendency (Gogel & Tietz 1973). From these and related observations it has been concluded that vergence information is too imprecise to play a signi¢cant role in everyday distance perception (see, for example, Brenner & van Damme 1998;Turvey & Soloman 1984).…”
Section: Introductionmentioning
confidence: 99%
“…the visual system's estimate of viewing distance, including the angular size of familiar objects (Gogel 1960;O'Leary and Wallach 1980;Predebon 1993), the pattern of binocular disparities (1) across a large field of view (Rogers and Bradshaw 1993;Bradshaw et al 1996), texture gradients (Gibson 1950;Sedgewick 1986), and the range of depths of objects visible in a scene and eye movements between these Brenner and van Damme 1998). From the results of experiments reported here, we argue that the instantaneous viewing conditions are not sufficient to explain the perceived depth of a stimulus: the past experience, or knowledge, of the observer may also have an influence, including experience under a particular set of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%